Her perfect twin - Bonner, Sarah (Grand Central Publishing, 2022)
"When Megan discovers photographs of her estranged identical twin sister on her husband's phone, she wants answers. Leah already has everything Megan has ever wanted. Fame, fortune, freedom to do what she wants. And when Megan confronts Leah, an argument turns to murder. The only way Megan can get away with killing her twin is to become her. But then lockdown hits. How can she continue living two lives? And what happens if someone else knows her secret too?"--